Islamic Religious Education Learning to Develop 4cs Through Blended Learning Method E-Poster Comment: Research at SMAN 27 Bandung City - Edi Prihadi; Supiana Supiana; Aan Hasanah; Asep Nursobah (Syntax Corporation Indonesia, 2021)
This research is motivated by the challenges of developing the Indonesian nation in the 21st century, namely preparing a young generation who is flexible, creative, and proactive. The young age needs to be formed so that they are skilled in problem-solving, wise in making decisions, thinking creatively, consulting, creating ideas effectively, and wor So that 21st-century skills or 4Cs need to be developed in learning, including PAI learning. This study aims to identify PAI learning to develop 4Cs at SMAN 27 Bandung and the effectiveness of PAI learning to develop 4Cs at SMAN. PAI learning is not limited to normative education obtained by memorizing. PAI is required to interpret and answer various current and future problems. PAI is needed to develop students' skills which include four skills, namely critical thinking skills, creative thinking skills, communication skills, and collaboration skills, especially in solving contemporary problems using the Islamic perspective. Thus PAI learning also has a great responsibility in developing 4Cs. Therefore, the task of educators is to condition learning so that all aspects of the 21st-century skills (Critical Thinking, Creative Thinking, Communication, and Collaboration) can be trained. The approach used in this research is qualitative with the descriptive-analytical method. Data were collected through observation, interviews, and documentation studies. The subjects of this study were teachers, students, school principals, and vice-principals in the field of curriculum. In general, PAI learning to develop 4Cs skills has been well implemented to achieve indicators of 4Cs skills. The PAI learning process to establish 4Cs at SMAN 27 Bandung City took place quite effectively, marked by the majority of students being enthusiastic in learning, which was marked by their seriousness in participating in learning, giving opinions during discussions responding to the views of their friends. Students understand the material quite well, characterized by providing statements and choosing one of the pictures according to the group questions in the e-poster and the reasons.